PENGARUH INFLUENCER MARKETING, CONTENT MARKETING, DAN SOCIAL MEDIA INSTAGRAM TERHADAP MINAT BELI PRODUK SIMCARD BYU TELKOMSEL PADA SISWA SMK NEGERI 1 KEDIRI - Muchamad Farel Mustaqiem; Ustadus Sholihin; Iing Sri Hardiningrum (Cahaya Ilmu Bangsa, 2024)
The development of internet progress is very dynamic, so the various technologies and features available to users are always changing, for example the emergence of various social media. In the field of technology, it is very useful for promotion-based businesses online. Medium promotional activities trend Nowadays, that is using a person influencer marketing and distribution of promotions using content marketing which can be promoted through social media instagram, These three factors can increase people's buying interest. The development of internet progress is very dynamic, so the various technologies and features available to users are always changing, for example the emergence of various social media. This research aims to explain (1) the influence influencer marketing against buying interest, (2) influence content marketing against buying interest, (3) influence social media instagram against buying interest, (4) influence influencer marketing, content marketing and social media instagram against buying interest. This type of research uses a quantitative approach. The sample for this research was 100 students of SMK Negeri 1 Kediri. The sampling technique uses purpose sampling. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple linear regression. The results of the research at the significance level show that: (1) there is a positive and significant influence influencer marketing on buying interest (2) there is a positive and significant influence content marketing on buying interest (3) there is a positive and significant influence social media instagram against buying interest (4) there is an influence influencer marketing, content marketing, and social media instagram simultaneously on buying interest. Keywords : Influencer Marketing; Content Marketing; Social Media Marketing; Buying Interest